Association between late‐life air pollution exposure and medial temporal lobe atrophy in older women. (20th December 2022) - Wang, Xinhui; Salminen, Lauren; Petkus, Andrew J.; Driscoll, Ira; Millstein, Joshua; Beavers, Daniel P.; Espeland, Mark A.; Braskie, Meredith N; Thompson, Paul M; Gatz, Margaret; Chui, Helena C; Resnick, Susan M.; et al.
Abstract: Background: Ambient air pollution exposures increase the risk of Alzheimer's disease (AD) and related dementias, which may be driven by structural brain alterations in the medial temporal lobe (MTL). The MTL consists of subregions critical for memory and vulnerable to AD neuropathology, including the hippocampus, parahippocampal gyrus (PHG), entorhinal cortex (ERC), and amygdala. However, previous structural MRI studies examining the hypothesized adverse effects of exposure on MTL were cross‐sectional and largely focused on hippocampus which yielded mixed results, failing to provide insights on the underlying neuropathological processes affected by air pollution exposures. Method: We conducted a longitudinal study including 653 cognitively‐normal community‐dwelling women from the Women's Health Initiative Memory Study with two MRI brain scans (MRI‐1: 2005‐6; MRI‐2: 2010‐11; Meanage at MRI‐1 = 77.3±3.5). Using regionalized universal kriging models, exposures at residential locations were estimated as 3‐year annual averages of fine particulate matter (PM2.5 ) and nitrogen dioxide (NO2; traffic‐related pollution) prior to MRI‐1. Volumes of the total MTL and MTL subregions were derived using multi‐atlas region segmentation with ensembled registration. We used linear regressions to estimate exposure effects on 5‐year standardized volume changes, adjusting for intracranial volume, sociodemographic, lifestyle, and clinical characteristics. We also examined if associations differed between APOE 4 carriers (n = 123) and non‐carriers (n = 463). Result: MTL volume decreased by 0.53±1.00cm 3 over 5 years. For each interquartile increase of PM2.5 (3.26µg/m 3 ) and NO2 (6.77ppb), adjusted MTL volume had greater shrinkage by 0.32cm 3 (95%CI = [‐0.43, ‐0.21]) and 0.12cm 3 (95%CI = [‐0.23, ‐0.01]) over 5 years, equivalent to respectively 17% (95%CI = [11%, 24%]) and 6% (95%CI = [0.6%, 12%]) increased dementia risk. For PHG, we found loss of 0.24cm 3 (95%CI = [‐0.30, ‐0.19]) and 0.09cm 3 (95%CI = [‐0.14, ‐0.04]) associated with PM2.5 and NO2 respectively. There was loss of 0.06cm 3 (95%CI = [‐0.10, ‐0.01]) in ERC associated with PM2.5, but not with NO2 . No associations were found with amygdala or hippocampal atrophy. The observed adverse exposure effects on MTL atrophy did not differ by APOE 4 genotype. Conclusion: MTL atrophy in older women was associated with late‐life exposures to PM2.5 and NO2, and the putative adverse effects varied across brain subregions. The PHG and ERC—the MTL subregions where AD neuropathologies likely begin, may be preferentially vulnerable to air pollution neurotoxicity.